2010
DOI: 10.1007/s10530-010-9729-4
|View full text |Cite
|
Sign up to set email alerts
|

Indirect ecological impacts of an invasive toad on predator–prey interactions among native species

Abstract: One of the many ways that invasive species can affect native ecosystems is by modifying the behavioural and ecological interactions among native species. For example, the arrival of the highly toxic cane toad (Bufo marinus) in tropical Australia has induced toad-aversion in some native predators. Has that shift also affected the predators' responses to native prey-for example, by reducing vulnerability of native tadpoles via a mimicry effect, or increasing vulnerability of other prey types (such as insects) vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…Cane toad sympatric fish displayed generalised aversion throughout the study which lasted for several months, indicating that generalised aversion acquired from exposure to cane toad tadpoles had a long-lasting effect on rainbowfish behaviour. These results support those of a previous study which demonstrated that experience with cane toads can produce a generalised aversion of similar prey types [40], [41]. The common planigale, Planigale maculata, is a small dasyurid that commonly feeds on frogs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cane toad sympatric fish displayed generalised aversion throughout the study which lasted for several months, indicating that generalised aversion acquired from exposure to cane toad tadpoles had a long-lasting effect on rainbowfish behaviour. These results support those of a previous study which demonstrated that experience with cane toads can produce a generalised aversion of similar prey types [40], [41]. The common planigale, Planigale maculata, is a small dasyurid that commonly feeds on frogs.…”
Section: Discussionsupporting
confidence: 91%
“…Planigale stopped feeding on frogs for up to 9 days following exposure to cane toads [40]. Similarly, lab experiments examining the effect of exposure to cane toad tadpoles in the northern trout gudgeon, Mogurnda mogurnda , showed a general shift away from native tadpoles [41]. Thus it seems likely that the toxic nature of the cane toad, even at the tadpole stage of the life cycle, is severe enough to generate aversion of similar prey types for considerable lengths of time.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of the chemically defended tadpoles in the assemblage may equate to the level of predator experience with such prey. This leads to generalised aversion to all tadpoles when defended tadpoles are often encountered (Nelson et al 2010; Caller and Brown 2013) and killing of defended tadpoles when they are rarely encountered (Kruse and Stone 1984; Nomura et al 2011). This generalised aversion may be prevented if the fish use a taste-and-refuse strategy to differentiate between prey types (Nelson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although here we focus on the effects resulting from unequal levels of defence against predators, the concept may be useful for tracking various interactions that are rather a by-product of current community composition than a consequence of selection for mimicking signals of another species. For animal communities, examples include ‘accidental mimicry’ between originally allopatric species or interactions between defended and undefended prey sharing an undiscriminating predator (Nelson et al 2010; Nesbit et al 2016; Wooster et al 2016; see also Robertson 2013, for ‘social traps’ resulting from coincidental visual resemblance in reef fish). Importantly, associational effects related to unequal defences in co-occurring species may in fact function as an incipient stage of the evolution of actual mimicry complexes (Mappes et al 1999; de Wert et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The birds readily consumed the alternative food items offered (except that pied herons and little egrets rarely ate native frog tadpoles) but all of the species that we tested -Nankeen night herons, purple swamphens, pied herons and little egrets-avoided both cane toad metamorphs and cane toad tadpoles. Likely, cane toads are unpalatable to wading birds, as they are to some other types of native predators, including fish (Crossland and Alford 1998;Crossland 2001;Nelson et al 2010b), marsupials Llewelyn et al 2010b) and snakes (Llewelyn et al 2010a). The only case of regular consumption of cane toads was by purple swamphens, in trays containing both toad metamorphs and fruit (rather than toads alone).…”
Section: Discussionmentioning
confidence: 99%